The Acute Effect of Insulin on Tissue Plasminogen Activator and Plasminogen Activator Inhibitor in Man - Landin, Kerstin; Tengborn, Lilian; Chmielewska, Joanna; Schenck, Henning von; Smith, Ulf (Thrombosis and Haemostasis, 1991)
The present study was performed to elucidate the acute effect of insulin on levels of tissue plasminogen activator (t-PA) and plasminogen activator inhibitor of endothelial cell type (PAI-1). Nine middle-aged, non-obese and non-smoking men were studied during a hyperinsulinemic, euglycemic glucose clamp for 2 h. Plasma insulin level during the clamp averaged 84 ± 12 mU/l and euglycemia was maintained at 4.9 ± 0.6 mmol/l. The t-PA activity gradually increased (75% mean increase after 2h, p <0.001) and the PAI-1 activity decreased (49% mean decrease after 2 h, p <0.001) during the clamp. t-PA activity decreased and PAI-1 activity increased after the insulin infusion was ceased, but they were still 48% higher and 38% lower, respectively, after 60 min. PAI-1 and t-PA activities were not affected by saline infusion for 2h.Thus, acute changes in the insulin levels lead to alterations rapid in the fibrinolytic system even when euglycemia is maintained. These effects may be induced by insulin itself or by the concomitant activation of the sympatho-adrenal system during the euglycemic clamp.